2018
DOI: 10.3390/ijms19113309
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structural Transformation Mechanism of Chinese and Thailand Silk Fibroin Fibers and Formic-Acid Fabricated Silk Films

Abstract: Silk fibroin (SF) is a protein polymer derived from insects, which has unique mechanical properties and tunable biodegradation rate due to its variable structures. Here, the variability of structural, thermal, and mechanical properties of two domesticated silk films (Chinese and Thailand B. Mori) regenerated from formic acid solution, as well as their original fibers, were compared and investigated using dynamic mechanical analysis (DMA) and Fourier transform infrared spectrometry (FTIR). Four relaxation event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 47 publications
0
30
1
Order By: Relevance
“…et al and Zhang et al [33,37]. While all these works have a similar sequence of process steps, they focus on different aspects of the FA/CaC 2 manufacturing chain [33][34][35][36][37] [35][36][37]. However, Zhang et al previously reported on the influence of dissolution of silk fibroin in FA/CaCl 2 on the molecular weight ratio and concluded that in comparison to common dissolution methods facilitating LiBr, CaCl 2 +EtOH, Ca(NO 3 ) 2 +MeHO or LiSCN, among others, the FA/CaCl 2 solvent rather showed decreased alterations in molecular weight [45].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…et al and Zhang et al [33,37]. While all these works have a similar sequence of process steps, they focus on different aspects of the FA/CaC 2 manufacturing chain [33][34][35][36][37] [35][36][37]. However, Zhang et al previously reported on the influence of dissolution of silk fibroin in FA/CaCl 2 on the molecular weight ratio and concluded that in comparison to common dissolution methods facilitating LiBr, CaCl 2 +EtOH, Ca(NO 3 ) 2 +MeHO or LiSCN, among others, the FA/CaCl 2 solvent rather showed decreased alterations in molecular weight [45].…”
Section: Discussionmentioning
confidence: 94%
“…The dissolution of silk fibroin using FA/CaCl 2 has been thoroughly investigated in several publications, such as Liu. et al and Zhang et al [33,37]. While all these works have a similar sequence of process steps, they focus on different aspects of the FA/CaC 2 manufacturing chain [33][34][35][36][37] [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies [17,144], formic acid was mixed with calcium chloride to break down natural silk by disrupting the native structure and breaking down carbon-carbon and carbon-nitrogen chains. Prolonged exposure to formic acid lowered the molecular weight of the silk and affected the thermal stability of the final biopolymer, including its glass transition temperature and region.…”
Section: Other Potential Solventsmentioning
confidence: 99%
“…A poor solvent will significantly affect the miscibility of protein or polysaccharide polymers and reduce the mechanical properties of the final materials [14][15][16]. In addition, many organic solvents will markedly alter the original molecular weight of protein materials such as silks [17]. Therefore, the use of ionic liquid (IL) is frequently applied for tuning the final properties of the material.…”
Section: Introductionmentioning
confidence: 99%